A Mixed-Method approach to explore Factors affecting Maternal and Infant Mortality in Uttarakhand: a pilot study - Prasuna Jelly; Suresh K Sharma; Vartika Saxena (Journal of Global Health Economics and Policy)
# Background Despite several efforts made to overcome the issues of delayed maternal care, there is need to explore cultural and socio-economic factors affecting maternal and infant mortality in Uttarakhand. # Methods A mixed-method study was conducted among 25 purposively selected families within one month of the postnatal period and eight conveniently selected healthcare workers from the selected rural areas of Rishikesh. A questionnaire was used to gather quantitative data from families regarding socioeconomic and cultural practices during perinatal period, along with factors contributing to mother and infant mortality. Followed by twelve mothers/family members were interviewed for qualitative data. Descriptive statistics was used for data analyses. # Results Restriction on diet during pregnancy, such as avoiding yellow-coloured fruits (90%), eating less food during pregnancy (95%), social restrictions during delivery (84%), and not feeding the infant for three days as they believed that the colostrum is not good for the baby (40%). # Conclusions The percentage of mothers whose practices are healthy for mother and baby are more than those of harmful practices. Efforts should be directed to motivate health-promotion practices. Among practices, there are numerous practices that are helpful to mothers and babies that should be encouraged, while harmful practices should be discouraged after appropriate rationalized education and motivation for the mother and families.